2008
DOI: 10.1093/geronb/63.1.p6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Predictors of Driving Cessation Among Older Adults From the ACTIVE Clinical Trial

Abstract: We examined the physical, visual, health, and cognitive abilities of 1,656 older adults as prospective predictors of self-reported driving cessation over a 5-year period. We examined the time to driving cessation across 5 years after we controlled for days driven per week at baseline and any cognitive intervention participation. Older age, congestive heart failure, and poorer physical performance (according to the Turn 360 Test) were statistically significant risk factors for driving cessation. Slower speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
137
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 41 publications
12
137
6
Order By: Relevance
“…Reduced speed of visual processing/attention (measured with UFOV score) was an independent risk factor in line with studies of driving cessation in aging. 29,30 The UPDRS-ADL score (risk factor for "ex-driver" status in a crosssectional study 31 ) and the daily total levodopa equivalent amount were independent risk factors of future driving cessation in the multivariate model suggesting that these measures better predict future functional impairment compared to the motor UPDRS score in the medicated ("on") phase.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced speed of visual processing/attention (measured with UFOV score) was an independent risk factor in line with studies of driving cessation in aging. 29,30 The UPDRS-ADL score (risk factor for "ex-driver" status in a crosssectional study 31 ) and the daily total levodopa equivalent amount were independent risk factors of future driving cessation in the multivariate model suggesting that these measures better predict future functional impairment compared to the motor UPDRS score in the medicated ("on") phase.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that slower processing speed predicts a greater likelihood of driving cessation within 5 years (Anstey, Windsor, Luszcz, & Andrews, 2006;Edwards et al, 2008). Processing speed measures such as the Digit Symbol Substitution test (Wechsler, 1981) predicted driving cessation, both independently and after adjusting for effects of age and self-rated health/physical function (Anstey, Windsor, et al, 2006;Edwards et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that slower processing speed predicts a greater likelihood of driving cessation within 5 years (Anstey, Windsor, Luszcz, & Andrews, 2006;Edwards et al, 2008). Processing speed measures such as the Digit Symbol Substitution test (Wechsler, 1981) predicted driving cessation, both independently and after adjusting for effects of age and self-rated health/physical function (Anstey, Windsor, et al, 2006;Edwards et al, 2008). Additionally, decline of processing speed (as well as general cognitive, verbal, and memory abilities) has been linked to increases in rates of falling and fall risk in elderly participants (Anstey, von Sanden, & Luszcz, 2006;Welmerink, Longstreth, Lyles, & Fitzpatrick, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A series of investigations demonstrated that reduced UFOV is a predictor of poor driving performance [21] and crash risk [22], and that the UFOV can be improved with training, leading to improved driving-related outcomes [23] and faster performance of timed IADLs [24]. Analyses of the speed-of-processing training arm in ACTIVE confirmed that individuals with reduced UFOV are at risk for imminent driving cessation [25] and that the intervention delayed the onset of driving cessation [26]. Additional studies demonstrated sustained improvement in cognitive self-efficacy [27], health-related quality of life [28], depressive symptoms [29], and health care expenditures [30].…”
Section: Recent Findings In Technology-enabled Cognitive Trainingmentioning
confidence: 99%